2008
DOI: 10.1210/en.2007-1372
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Destabilization of β-Catenin Augments Apoptosis of High-Glucose-Stressed Mesangial Cells

Abstract: Intense mesangial cell apoptosis contributes to the pathogenesis of diabetic nephropathy. Although reactive oxygen radicals and Wnt signaling components are potent regulators that modulate renal tissue remodeling and morphogenesis, cross-talk between oxidative stress and Wnt/beta-catenin signaling in controlling high-glucose-impaired mesangial cell survival and renal function have not been tested. In this study, high glucose induced Ras and Rac1 activation, superoxide burst, and Wnt5a/beta-catenin destabilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…Furthermore, treatment with simvastatin restored Wnt4, Wnt5a and β-catenin expression in MCs and attenuated diabetic kidney injuries both in vivo and in vitro (16). In addition, it has been demonstrated that abrogation of oxidative stress may restore Wnt5a/β-catenin signaling and attenuate high glucose-induced MC apoptosis (25). DKK-1 expression was also increased in these same conditions, and mediated c-Jun, TGF-β1, and fibronectin expression, whereas stable β-catenin expression alleviated DKK-1-induced profibrotic factors, indicating that β-catenin may be a potential therapeutic target of MC dysfunction of diabetic nephropathy (26).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, treatment with simvastatin restored Wnt4, Wnt5a and β-catenin expression in MCs and attenuated diabetic kidney injuries both in vivo and in vitro (16). In addition, it has been demonstrated that abrogation of oxidative stress may restore Wnt5a/β-catenin signaling and attenuate high glucose-induced MC apoptosis (25). DKK-1 expression was also increased in these same conditions, and mediated c-Jun, TGF-β1, and fibronectin expression, whereas stable β-catenin expression alleviated DKK-1-induced profibrotic factors, indicating that β-catenin may be a potential therapeutic target of MC dysfunction of diabetic nephropathy (26).…”
Section: Discussionmentioning
confidence: 94%
“…In podocyte injury and proteinuric kidney diseases, the Wnt pathways are essential regulators and potential therapeutic targets (13,14). Studies regarding the role of the Wnt signaling pathway in MCs have mainly focused on hyperglycemic conditions (15,16,25,26). Lin et al (15) observed that in diabetic nephropathy, the Wnt/β-catenin signaling pathway serves a crucial role in the regulation of MC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Although several groups have identified markers of oxidative stress and oxidative damage in diabetic kidneys or kidney cells (3,4), no studies to date have attempted to measure and quantify superoxide production with diabetes directly in vivo. As the half-life of superoxide anion in cells is measured in seconds and it is rapidly converted to hydrogen peroxide and other reactive oxygen intermediates, the measurement of superoxide production has been challenging (5), especially in the intact organism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, renal proximal tubular cells (47), podocytes (61), and MC (23) exhibit apoptosis after exposure to high glucose concentrations, and an increase in TUNEL-positive cells has been observed in experimental and clinical diabetic nephropathy (30,64,70), although a link to flux through the hexosamine pathway has not been established. Accordingly, we studied the relationship between flux through the hexosamine pathway and MC proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%